Cruces y caminos de las antologías poéticas uruguayas - Rocca, Pablo (Anales de Literatura Hispanoamericana, 2004)
Through an examination of poetry anthologies, this is essay studies the dynamics of Uruguay's literary and cultural production within a national and international social and economic context. This entails a critical reappraisal of the stability of concepts such as nation, anthology and canon. The overview begins in the origin of the Uruguayan State and ends in the present. An appendix includes a bibliographical index of Uruguayan poetry anthologies, with a methodological introduction.